Editorial for Special Issue “Remote Sensing of Precipitation: Part III" - Michaelides, Silas (My University, 2023)
This Special Issue of Remote Sensing, which is the third in a series entitled “Remote Sensing of Precipitation”, comprises a collection of ten papers devoted to remote sensing applications for measuring precipitation; these include new satellite technologies for the remote sensing of precipitation, the validation of satellite-based precipitation estimates using rain gauge measurements and surface radar estimates, and comparisons between gridded precipitation data. The next section summarizes the individual articles presented in this Special Issue, in alphabetical order based on the first author’s name.